2001
DOI: 10.1139/f00-257
|View full text |Cite
|
Sign up to set email alerts
|

Examining feeding strategies and position choice of drift-feeding salmonids using an individual-based, mechanistic foraging model

Abstract: We demonstrated the ability of a mechanistic habitat selection model to predict habitat selection of brown trout (Salmo trutta) and mountain whitefish (Prosopium williamsoni) during summer and winter conditions in the Blacksmith Fork River, Utah. By subtracting energy costs and losses from the gross energy intake rate (GEI) obtained through simulation of prey capture, the model calculates the potential net energy intake rate (NEI) of a given stream position, which is essentially the rate of energy intake avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 24 publications
3
72
0
1
Order By: Relevance
“…To account for direct flow-dependence in foraging by shovelnose sturgeon (Modde and Schmulbach, 1977;Seibert et al, 2011), we use the drift foraging model by Guensch et al (2001) to calculate the realized encounter rate (Eprey,i and Eintra); drift-feeding sturgeon are assumed to encounter and capture prey within an area defined by fish swimming speed and water velocity. Eprey,i and Eintra are calculated by a randomly drawn number from a Poisson distribution with potential encounter rate (ERprey i or intra, number • s -1 ) as the number of trials, calculated as…”
Section: Management Implications For Riverine Fish Recruitment In Regmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for direct flow-dependence in foraging by shovelnose sturgeon (Modde and Schmulbach, 1977;Seibert et al, 2011), we use the drift foraging model by Guensch et al (2001) to calculate the realized encounter rate (Eprey,i and Eintra); drift-feeding sturgeon are assumed to encounter and capture prey within an area defined by fish swimming speed and water velocity. Eprey,i and Eintra are calculated by a randomly drawn number from a Poisson distribution with potential encounter rate (ERprey i or intra, number • s -1 ) as the number of trials, calculated as…”
Section: Management Implications For Riverine Fish Recruitment In Regmentioning
confidence: 99%
“…where ΔѲ is an incremental angle perpendicular to the flow vector (MCA is divided into 10 equal segments, Guensch et al, 2001), and MCDi is the maximal capture (or competition) distance (m).…”
Section: Management Implications For Riverine Fish Recruitment In Regmentioning
confidence: 99%
“…More physicallybased models of fish habitat use (e.g. Guensch et al, 2001;Booker et al, 2004) also have potential to improve environmental flow methods (Hardy, 1998).…”
Section: Hydraulic Habitat Analysis and Modellingmentioning
confidence: 99%
“…The authors suggested that by creating more feeding sites that are energetically favourable for trout during summer, boulders may indirectly enhance their body condition and thus overwinter survival. The energy-optimization utility of these foraging sites has been revealed by simple intake rate/growth maximization models which try to predict habitat selection by salmonids in experimental streams (FAUSCH, 1984) and in the field (HUGHES and DILL, 1990;HUGHES, 1992;GUENSCH et al, 2001). These models showed that individuals ranked positions according to their potential profit by combining hydraulic, drift and other biological parameters (detection distance of prey, presence of competitors).…”
Section: Normal Conditionsmentioning
confidence: 99%